2019
DOI: 10.1080/00346764.2019.1630667
|View full text |Cite
|
Sign up to set email alerts
|

Does unemployment aggravate suicide rates in South Africa? Some empirical evidence

Abstract: Our study investigates the cointegration relationship between suicides and unemployment in South Africa using annual data collected between 1996 and 2015 applied to the ARDL model. Furthermore, our empirical analysis is gender and age specific in the sense that the suicide data is disintegrated into different 'sex' and 'age' demographics. Our empirical results indicate that unemployment is insignificantly related with suicide rates with the exception for citizens above 75 years. On the other hand, other contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Their findings showed that economic expansion in society tends to have a bigger impact on lowering the suicide rates than economic recession on increasing it for people who were above the age of 45. Phiri and Mukuka (38) used the ARDL model to analyze the assimilation between unemployment and suicide in South Africa from 1996 to 2015. Their findings show that, contrary to the evidence illustrated by other countries, unemployment is not primarily dependent on suicide rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings showed that economic expansion in society tends to have a bigger impact on lowering the suicide rates than economic recession on increasing it for people who were above the age of 45. Phiri and Mukuka (38) used the ARDL model to analyze the assimilation between unemployment and suicide in South Africa from 1996 to 2015. Their findings show that, contrary to the evidence illustrated by other countries, unemployment is not primarily dependent on suicide rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thirdly, studies on suicides have been dominated by psychological sciences, which primarily depend on longitudinal analytical techniques. It is only more recently that academics have considered the use of adequate time series analysis (see Platt 1984;Platt, Micciolo, and Tansella 1992;and Phiri and Mukuku 2020 for a comprehensive review of the empirical literature).…”
Section: Introductionmentioning
confidence: 99%
“…A policy question which demands empirical attention is whether policymakers are currently in control of prevailing levels of suicides globally. Currently, a majority of the economic literature has examined the relationship between suicides and other economic factors such as income (Chuang and Huang 1997;Brainerd 2001;Neumayer 2003), unemployment (Andres 2005;Dahlberg and Lundin 2005;Phiri and Mukuku 2020), or divorce (Chuang and Huang 1997;Neumayer 2003;Andres 2005). Other stud-ies have even designed a so-called 'natural rate of suicides', a concept which assumes that suicides could never be zero, regardless of how ideal socioeconomic conditions are Yang and Lester (1991;, Viren (1999) and Andres and Halicioglu (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Though it is widely recognized that periods of financial hardship may be accompanied by increased suicide rates, it should be noted that some inconsistent results are to be found in the literature. On the one hand, several authors have pointed to this association [11][12][13][14][15][16][17][18]; on the other, other authors have questioned it [19] or reported no association at all in some countries [20][21][22][23][24]. Such mixed results and inconsistencies may be explained by the heterogenity of the statistical methods used, not always appropriate for the type of data included in the analyses [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…[Please display Figure 1 about here] Econometric analysis is problematic due to some features of suicide and unemployment rates. Unitroot features frequently affecting such measures make them unfit for the inclusion in Ordinary Least Squares (OLS) regressions, due to the risk of spurious associations [18,25,27]. As a result, cointegration techniques are useful to overcome such limitations, when dealing with time series data.…”
Section: Introductionmentioning
confidence: 99%